2020
DOI: 10.1007/s11738-020-03099-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lignosulphonates on Vanilla planifolia shoot multiplication, regeneration and metabolism

Abstract: Vanilla planifolia (V. planifolia) is a valuable orchidaceous plant, commonly grown for its pods that are used to produce the flavouring vanilla extract. Here, we evaluated the effect of calcium lignosulphonate (Ca-LIGN) and sodium lignosulphonate (Na-LIGN) on multiplication and regeneration of V. planifolia shoot tip culture. In 150 mg L−1 Ca-LIGN medium, the most number of shoots per explant (5.78 ± 0.63) was successfully obtained. Besides, Ca-LIGN also enhanced the shoot bud and primordial formation rate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previously, plant elicitors, either biotic or abiotic, had been employed to stimulate plant growth for better yield production 9 . This included the usage of elicitors such as carrageenan, chitosan, β-Aminobutyric acid, lignosulfonate and beneficial micro-organisms [9][10][11] . Carrageenan is a naturally occurring high molecular weight polysaccharide, which is extracted from edible red seaweed (Rhodophyta) 11 .…”
mentioning
confidence: 99%
“…Previously, plant elicitors, either biotic or abiotic, had been employed to stimulate plant growth for better yield production 9 . This included the usage of elicitors such as carrageenan, chitosan, β-Aminobutyric acid, lignosulfonate and beneficial micro-organisms [9][10][11] . Carrageenan is a naturally occurring high molecular weight polysaccharide, which is extracted from edible red seaweed (Rhodophyta) 11 .…”
mentioning
confidence: 99%
“…Con relación a la longitud de raíz evaluada a los 90 d, el tratamiento de 1,75 mg/L de BAP promovió la mayor longitud de las raíces con un promedio 5 cm, mientras que en nuestro laboratorio resultados previos indicaron una longitud radical de 1,74 cm cuando se aplicó la concentración de 1 mg/L. Wan Abdullah et al (2020) aplicaron 1 mg/L de BAP en V. planifolia obteniendo 0,83 ± 0,21 cm de longitud de raíces promedio en el tratamiento control. Con el avance en el conocimiento de las condiciones óptimas de cultivo in vitro de V. tahitensis se abren las posibilidades para desarrollar protocolos eficientes para la micropropagación in vitro de esta orquídea con alta perspectiva en el mercado comercial gourmet debido a sus características específicas.…”
Section: Discussionunclassified
“…In addition, study by Docquier et al 10 suggested that incorporation of CaLS in the medium was able to enhance the nutrient ion availability to the plant, leading to better nutrient ion acquisation and growth performance of orchid, poplar and California redwood. Recent study by Wan Abdullah et al 14 also demonstrated that incorporation of CaLS improved the shoot proliferation rate of in vitro vanilla plant. The increased in vanilla shoot proliferation rate was associated with enhanced chlorophyll content, that contributed to the better photosynthetic activity for plant growth.…”
Section: Introductionmentioning
confidence: 91%